Consumption Activities and Consumption Literacy in Homeschooling Students: Analysis of Consumptive Behavior - Lidwina Apriani Paskalita; Achmadi Achmadi; Syamsuri Syamsuri; Maria Ulfah; Okianna Okianna (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study is motivated by the growing phenomenon of consumptive behavior among students, particularly within the alternative educational setting of homeschooling. A lack of practical, baseline ability to differentiate between needs and wants, paired with high exposure to digital environments, serves as the primary catalyst for this research. This study formally aims to analyze the conceptual understanding of consumption, evaluate consumption literacy levels and explore their relationship with the consumptive behavior patterns of homeschooling students at PKBM Bina Mulia. Adopting a qualitative case study design, this research involved eight purposively selected informants: three students, three parents and two educators. Data were gathered through semi structured interviews and analyzed using the Miles and Huberman model, encompassing data reduction, data display and conclusion verification. The results indicate that while students possess a fundamental cognitive understanding of the difference between needs and wants, its real world application remains inconsistent, particularly among younger cohorts. Students consumption literacy is still constrained in its ability to filter information, there by inducing impulsive consumptive behavior and a tendency to follow online shopping trends. Crucially, consumption literacy is confirmed to function as an essential cognitive filter mediating knowledge into rational economic actions. Enhancing conceptual understanding and sharpening consumption literacy though active parental mediation are vital to fostering more rational, critical and responsible economic behavior among alternative education students.